Genomic Uniqueness of Local Sheep Breeds From Morocco - Ouhrouch, Abdessamad; Boitard, Simon; Boyer, Frédéric; Servin, Bertrand; Da Silva, Anne; Pompanon, François; Haddioui, Abdelmajid; Benjelloun, Badr (Frontiers in Genetics, 2021)
Sheep farming is a major source of meat in Morocco and plays a key role in the country's agriculture. This study aims at characterizing the whole-genome diversity and demographic history of the main Moroccan sheep breeds, as well as to identify selection signatures within and between breeds. Whole genome data from 87 individuals representing the five predominant local breeds were used estimate their level of neutral genetic diversity and to infer the variation of their effective population size over time . In addition, we used two methods to detect selection signatures: either for detecting selective sweeps within each breed separately or by detecting differentially selected regions by contrasting different breeds. We identified hundreds of genomic regions putatively under selection, which related to several biological terms involved in local adaptation or the expression of zootechnical performances such as Growth, UV protection, Cell maturation or Feeding behavior. The results of this study revealed selection signatures in genes that have an important role in traits of interest and increased our understanding of how genetic diversity is distributed in these local breeds. Thus, Moroccan local sheep breeds exhibit both a high genetic diversity and a large set of adaptive variations, and therefore, represent a valuable genetic resource for the conservation of sheep in the context of climate change.